Adoption of Digital Technology and Sales Performance Improvement among Indonesian SMEs: A Mixed-Methods Analysis - Naibaho, Ronald; Effiyaldi, Effiyaldi; Nurhadi, Nurhadi; Suratno, Eddy; Pasaribu, Johni Paul Karolus (PT Mattawang Mediatama Solution, 2025)
This research aims to analyze the impact of digital technology adoption and digital literacy on improving the sales performance of MSMEs in Indonesia, with customer satisfaction as a mediating variable. A quantitative approach was used with the path analysis method on 200 MSME actors from four different provinces. Data were collected through closed questionnaires and analyzed using SmartPLS. The results of the study show that both digital technology adoption and digital literacy have a positive and significant effect on customer satisfaction. Customer satisfaction was also proven to play a significant mediating role in improving sales performance. The R-square value of 0.607 indicates that the model has a sufficiently high explanatory power for the dependent variable. These findings confirm that the success of MSME digitalization does not only depend on the use of technological tools, but also on the understanding of business actors in managing customer service digitally. The government and stakeholders need to provide strategic interventions through digital literacy training, infrastructure provision, and inclusive sector-based policies. This research provides an empirical contribution to the digital entrepreneurship literature, as well as practical implications for the development of MSMEs in the era of digital economic transformation. Further research is recommended to add variables such as customer loyalty and operational efficiency to the model, and to apply a longitudinal approach to observe the long-term impact of digital technology adoption.